Semi-automatic vertical type high-frequency quenching equipment - CUI LIZHUANG (2018)
The invention relates to semi-automatic vertical type high-frequency quenching equipment. The equipment comprises a base, a water tank, a bracket, a lifting motor, a lifting table, a rotating motor, an annular spray pipe, a workpiece fixing seat and a quenching equipment body. The semi-automatic vertical type high-frequency quenching equipment has the advantages that the design is scientific, thestructure is reasonable, the use is convenient and the automation degree is higher, compared with a traditional manual operation mode, the automation degree of the equipment is higher, the machining processes are less affected by human factors, after the equipment is used, the working efficiency can be improved, the quality of products is improved, the rejection rate is reduced, the manpower and raw material cost are reduced for enterprises. 本发明涉及种半自动立式高频淬火设备，包括基座、水箱、支架、升降电机、升降台、转动电机、环形喷水管、工件固定座以及淬火设备。本发明是种设计科学、结构合理、使用方便、自动化程度较高的半自动立式高频淬火设备，与传统手工操作方式相比，本设备的自动化程度较高，加工过程受人为因素影响较少，使用本设备后能够提高工作效率、提高产品质量、降低废品率，为企业节省人力及原材料成